REORIENTASI PERAN DAN FUNGSI GURU PENDIDIKAN AGAMA ISLAM DALAM PERSPEKTIF SOSIOLOGI PENDIDIKAN ISLAM - Irfan Awalludin; Nur Hikmatusuriah; Muhammad Abdullah Darraz (LPPM STAI Muhammadiyah Probolinggo, 2026)
Rapid social change, advancements in digital technology, and shifting educational policies compel Islamic Religious Education (PAI) teachers to redefine their roles and functions. PAI teachers are no longer merely instructors delivering subject matter; they also support and inspire students, act as agents of positive social change, and serve as role models in shaping student attitudes and character. This study aims to analyze the evolving roles and functions of PAI teachers from the perspective of the sociology of Islamic education and to examine the impact of these changes on contemporary educational processes. A library research method was employed, involving the review of relevant literature. The findings indicate that changes in PAI teaching methods have positively influenced the quality of learning and teacher professionalism, while also strengthening student character, promoting religious moderation, fostering a religiously grounded school culture, enhancing digital literacy, and improving the ability of both teachers and students to adapt to 21st-century social changes. Consequently, redefining the role of PAI teachers is essential to creating an Islamic education system that is responsive to needs and circumstances while remaining capable of continuous evolution.